2020
DOI: 10.1038/s41467-020-18268-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of MRSA-infected osteomyelitis using bacterial capturing, magnetically targeted composites with microwave-assisted bacterial killing

Abstract: Owing to the poor penetration depth of light, phototherapy, including photothermal and photodynamic therapies, remains severely ineffective in treating deep tissue infections such as methicillin-resistant Staphylococcus aureus (MRSA)-infected osteomyelitis. Here, we report a microwave-excited antibacterial nanocapturer system for treating deep tissue infections that consists of microwave-responsive Fe3O4/CNT and the chemotherapy agent gentamicin (Gent). This system, Fe3O4/CNT/Gent, is proven to efficiently tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
121
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 193 publications
(137 citation statements)
references
References 41 publications
1
121
0
Order By: Relevance
“…Studies have reported that prussian blue nanoparticles synthesized as photosensitive hydrogels exhibiting strong photothermal properties under NIR irradiation resulted in the capture of bacteria in hydrogels and its further killing by perturbation of bacterial cell membranes in S. aureus (99.97%) and E. coli (99.93%) (Han et al, 2020b). Similar results were observed in MRSA-infected osteomyelitis to treat tissue infections using magnetically iron oxide-targeted carbon nanotubes (Fe 2 O 3 /CNT), resulting in microwave-assisted bacterial killing (Qiao et al, 2020). However, more studies are needed to further reduce the cytotoxicities of PANs.…”
Section: Controlled Release Of Photothermal Agentsmentioning
confidence: 61%
“…Studies have reported that prussian blue nanoparticles synthesized as photosensitive hydrogels exhibiting strong photothermal properties under NIR irradiation resulted in the capture of bacteria in hydrogels and its further killing by perturbation of bacterial cell membranes in S. aureus (99.97%) and E. coli (99.93%) (Han et al, 2020b). Similar results were observed in MRSA-infected osteomyelitis to treat tissue infections using magnetically iron oxide-targeted carbon nanotubes (Fe 2 O 3 /CNT), resulting in microwave-assisted bacterial killing (Qiao et al, 2020). However, more studies are needed to further reduce the cytotoxicities of PANs.…”
Section: Controlled Release Of Photothermal Agentsmentioning
confidence: 61%
“…Combining the magnetic targeting and MCT, Wu et al constructed a dual-targeting and MV-responsive nanocarriers for precise and synergistic therapy for combating MRSA-induced osteomyelitis (Fig. 12 ) [ 73 ]. Briefly, mesoporous iron oxide NPs were modified with dielectric carbon nanotubes (CNTs) with good MV absorption ability to obtain neural-network-like Fe 3 O 4 /CNT.…”
Section: Nanocarriers Responsive To External Stimulimentioning
confidence: 99%
“…Osteomyelitis is a difficult-to-treat bone disease often caused by a bacterial infection following a fracture or surgery. (1). It has been reported that up to 30% of high-risk open fractures will be infected, which could progress to organ infection, bone destruction, and sepsis, and is life-threatening (2,3).…”
Section: Introductionmentioning
confidence: 99%